2015
DOI: 10.1261/rna.049122.114
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in temperature within the physiologic range modify strand-specific expression of select human microRNAs

Abstract: Previous studies have revealed that clinically relevant changes in temperature modify clinically relevant gene expression profiles through transcriptional regulation. Temperature dependence of post-transcriptional regulation, specifically, through expression of miRNAs has been less studied. We comprehensively analyzed the effect of 24 h exposure to 32°C or 39.5°C on miRNA expression profile in primary cultured human small airway epithelial cells (hSAECs) and its impact on expression of a targeted protein, prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 92 publications
0
16
0
Order By: Relevance
“…Therefore, we acknowledge that hypothermia may have contributed to the gene expression patterns. Although we cannot completely exclude that some of the differentially expressed genes were stimulated by hypothermia, preclinical evidence has shown that a reduction by 4–10°C for over 6 h was required to influence gene expression in animal models [28-32]. Moreover, none of the hypothermia-inducible genes were found to be significantly differently expressed between neonatal encephalopathy and control babies [33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we acknowledge that hypothermia may have contributed to the gene expression patterns. Although we cannot completely exclude that some of the differentially expressed genes were stimulated by hypothermia, preclinical evidence has shown that a reduction by 4–10°C for over 6 h was required to influence gene expression in animal models [28-32]. Moreover, none of the hypothermia-inducible genes were found to be significantly differently expressed between neonatal encephalopathy and control babies [33].…”
Section: Discussionmentioning
confidence: 99%
“…We [13][14][15][16] and others [17,18] have shown that modest deviations in temperature within the clinically relevant range impact cell survival and function of lung epithelium, including regulation of the heat shock response. Specifically, exposure to febrile-range temperature ($39.5 C) sensitises lung epithelium to Fas-associated protein with death domain (FADD)/caspase-8-dependent apoptosis [13,17] and stimulates submaximal heat shock factor-1 (HSF1) activation and heat shock protein (HSP)-72 expression [16].…”
Section: Introductionmentioning
confidence: 89%
“…Transfection with miRNA mimics and inhibitors HEK293T cells were transfected with miRNA mimics and inhibitors as we have previously described [14]. Briefly, cells were seeded in six-well cell culture plates (BD Biosciences) and transfected 24 h later.…”
Section: Gene Primer Name Amentioning
confidence: 99%
See 1 more Smart Citation
“…Given that cellular environment may influence the process of miRNA strand selection, (33,34) we asked whether a correlation exists between expression of miR-122 and miR-122* in different physiological settings. We measured the levels of both strands in human serum and in the corresponding liver biopsies and in liver tumors derived from Mdr2-KO mice (an inflammation-induced HCC model).…”
Section: Mir-122* Is a Liver-specific Mirnamentioning
confidence: 99%